A method for fast timer coding of texts - Skuratovskii, R. V. (Cybernetics and systems analysis, 2013)
A statistics-oriented data compression method based on unconventional timer encryption is developed. Necessary complexity estimates are made. The method can be used to compress sms messages. A probabilistic analysis is performed and its efficiency is evaluated. The theoretical data compression rate is the world’s highest. The time complexity is determined, which can be used to find the archiving time taking into account the frequency of the text generator.